PERSPECTIVES ON FERTILITY PACIENTECON BREAST CANCER GENITO. PROPOSAL FOR A CLASSIFICATION OF COMMITMENT OF FERTILITY BY THERAPEUTIC ONCOLOGY - Cúneo, Nicasio (2015)
The inevitable negative psychical, physical and social impact of oncological treatment on young women’s fertility obliges us to know in detail the reproductive function preserving techniques. In this paper we approach both the anatomical and physiological compromises and propose a classification of fertility involvement by oncological therapies.